2020
DOI: 10.3747/co.27.5267
|View full text |Cite
|
Sign up to set email alerts
|

Does Free nicotine Replacement Improve Smoking Cessation Rates in Cancer Patients?

Abstract: Background Cigarette smoking is carcinogenic and has been linked to inferior treatment outcomes and complication rates in cancer patients. Here, we report the results of an 18-month pilot smoking cessation program that provided free nicotine replacement therapy (nrt).Methods In January 2017, the smoking cessation program at our institution began offering free nrt for actively cigarette-smoking patients with cancer. The cost of 4 weeks of nrt was covered by the program, and follow-up was provided by smoking ces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 19 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…Of the 43 studies, 10 (23%) were RCTs and 33 (77%) were nonrandomized study designs . The majority of studies were conducted in the US (n = 34; 79%) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 43 studies, 10 (23%) were RCTs and 33 (77%) were nonrandomized study designs . The majority of studies were conducted in the US (n = 34; 79%) .…”
Section: Resultsmentioning
confidence: 99%
“…The nonrandomized controlled trials generally had a low risk of confounding, selection, classification, and reporting bias, with moderate bias in measurement and mixed performance and attrition bias (eTable 5 in Supplement 2). The 10 studies showing a moderate overall bias resulted from unblinded outcome assessors (D6), patient outcome data missing (D5), lack of patient adherence (D4), gap in data collection (D2), and different intervention components across implementation sites (ie, opt-out approach) (D1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This has led to several natural experiments and an attempt to identify best implementation practices for smoking cessation in cancer care settings [ 8 ]. For example, in 2017, the London Regional Cancer Program launched a pilot to provide free nicotine replacement therapy (NRT) to improve the low referral rates identified in an evaluation of their smoking cessation program [ 9 , 10 ]. The pilot demonstrated that provision of free NRT significantly improved referral rates, and most referred patients either reduced their cigarette smoking or quit completely.…”
Section: Introductionmentioning
confidence: 99%